2021
DOI: 10.1155/2021/2330417
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Adrenal Insufficiency in Patients with Multiple Myeloma Receiving Long-Term Chemotherapy including Corticosteroids: A Retrospective Cohort Study

Abstract: Multiple myeloma (MM) is the second most common hematologic malignancy and requires long-term and high-dose corticosteroid-based chemotherapy. The aim of this study was to investigate the prevalence and clinical predictors of corticosteroid-associated adrenal insufficiency (AI) in patients with MM receiving long-term chemotherapy. This retrospective study included patients with MM who were administered corticosteroid-based chemotherapy and underwent a rapid adrenocorticotropic hormone (ACTH) stimulation test b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…We assume that this was because patients with multiple myeloma tend to receive repeated treatments with salvage regimens including high-dose glucocorticoids. 19 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that this was because patients with multiple myeloma tend to receive repeated treatments with salvage regimens including high-dose glucocorticoids. 19 20 …”
Section: Discussionmentioning
confidence: 99%
“… 4 25 26 Our finding is consistent with these previous findings. In terms of megestrol acetate, only a few case reports 27 28 29 and one recent retrospective study 20 reported the history of megestrol acetate use as a risk factor for AI. Through multivariable analysis that adjusted for confounding variables, our study provides further evidence that megestrol acetate could cause AI in patients with malignancy.…”
Section: Discussionmentioning
confidence: 99%